Konflikt w cyberprzestrzeni na przykładzie wojny w Ukrainie. Studium aktywności z lat 2022–2023 - Goryń, Kamil (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
Contemporary international conflicts are marked by their dynamic nature and diversity, which makes it challenging to categorise them, particularly regarding warfare and cyber operations that fall below the threshold of armed conflict. This article examines the conflict in cyberspace during the war in Ukraine, highlighting how cyber operations support kinetic actions and disinformation campaigns.
p. 191-204
Summary in English and Russian.
Keywords: disinformation operations of the Russian Federation; digital security; war in Ukraine; Russian invasion of Ukraine 2022; disinformation - Russia - 1990-; disinformation - Ukraine - 1990-; information warfare - Russia (Federation); cyberterrorism - 1990-